Pelatihan Manajemen Pemasaran Untuk Meningkatkan Usaha Komplang Ikan di Jln. Pasundan 2 RT 05 RW 01 Kelurahan Sumber Jaya Kecamatan Kampung Melayu - Noviantoro, Rinto; Fitriano, Yun; Santri, Dila; Anggini, Anggini; Sari, Yana Nopita (Jurnal Dehasen Mengabdi, 2022)
Marketing management is a well-planned, organized, coordinated and supervised marketing activity that will produce satisfactory results. But at this time there are still a lot of komplang fish businesses that have not been able to manage marketing properly and correctly. There are several factors that cause this komplang fish business not to manage marketing properly and correctly, one of which is their ignorance of science and knowledge and they do not know where to start to manage marketing properly and correctly. Therefore, our dedication team for university lecturers and accounting students provides simple marketing management training, especially practicing the 4p theory marketing mix which will improve the quality of marketing for the komplang fish business. The method used is socialization in the form of inauguration, discussion, and marketing mix practices. The results of this service are very helpful for business owners of komplang fish in marketing management.